Clinical and Genomic Characterization of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2) Infections in mRNA Vaccinated Health Care Personnel in New York City. (13th October 2021) - Robilotti, Elizabeth V; Whiting, Karissa; Lucca, Anabella; Poon, Chester; Guest, Rebecca; McMillen, Tracy; Jani, Krupa; Solovyov, Alexander; Kelson, Suzanne; Browne, Kevin; Freeswick, Scott; Hohl, Tobias M; et al.
Abstract: Background: Vaccine-induced clinical protection against severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) variants is an evolving target. There are limited genomic level data on SARS CoV-2 breakthrough infections and vaccine effectiveness (VE) since the global spread of the B.1.617.2 (Delta) variant. Methods: In a retrospective study from 1 November 2020 to 31 August 2021, divided as pre-Delta and Delta-dominant periods, laboratory-confirmed SARS CoV-2 infections among healthcare personnel (HCP) at a large tertiary cancer center in New York City were examined to compare the weekly infection rate-ratio in vaccinated, partially vaccinated, and unvaccinated HCP. We describe the clinical and genomic epidemiologic features of post-vaccine infections to assess for selection of variants of concern (VOC)/variants of interest (VOI) in the early post-vaccine period and impact of B.1.617.2 (Delta) variant domination on VE. Results: Among 13658 HCP in our cohort, 12379 received at least 1 dose of a messenger RNA (mRNA) vaccine. In the pre-Delta period overall VE was 94.5%. Whole genome sequencing (WGS) of 369 isolates in the pre-Delta period did not reveal a clade bias for VOC/VOI specific to post-vaccine infections. VE in the Delta dominant phase was 75.6%. No hospitalizations occurred among vaccinated HCP in the entire study period, compared to 17 hospitalizations and 1 death among unvaccinated HCP. Conclusions: Findings show high VE among HCP in New York City in the pre-Delta phase, with moderate decline in VE post-Delta emergence. SARS CoV-2 clades were similarly distributed among vaccinated and unvaccinated infected HCP without apparent clustering during the pre-Delta period of diverse clade circulation. Strong vaccine protection against hospitalization was maintained through the entire study period. Abstract : study of >13000 healthcare personnel (HCP) showed that messenger RNA (mRNA) vaccine effectiveness (VE) against coronavirus disease 2019 (COVID-19) was 94% through initial 5 months of follow-up, with moderate VE reduction to 75% during subsequent Delta-dominant period. No hospitalizations occurred among vaccinated HCP throughout the study period.